2023
DOI: 10.3389/fphys.2023.1167449
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of post-match recovery in semi-professional and professional football (soccer)

Abstract: High-level football (soccer) players face intense physical demands that result in acute and residual fatigue, impairing their physical performance in subsequent matches. Further, top-class players are frequently exposed to match-congested periods where sufficient recovery times are not achievable. To evaluate training and recovery strategies, the monitoring of players’ recovery profiles is crucial. Along with performance and neuro-mechanical impairments, match-induced fatigue causes metabolic disturbances deno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 277 publications
(532 reference statements)
0
1
1
Order By: Relevance
“…Although previous studies reported an increase in CK, AST, and ALT up to 48–72 h after a professional soccer game ( 3 , 60 ), our data do not corroborate these findings. Protein supplementation might have attenuated the increase in CK levels after the game.…”
Section: Discussioncontrasting
confidence: 99%
“…Although previous studies reported an increase in CK, AST, and ALT up to 48–72 h after a professional soccer game ( 3 , 60 ), our data do not corroborate these findings. Protein supplementation might have attenuated the increase in CK levels after the game.…”
Section: Discussioncontrasting
confidence: 99%
“…Recovery from severe lengthening contractions (e.g., squats or drop jumps) also causes biomarkers in serum blood to peak within the following days. Proteins and metabolic-related enzymes such as creatine kinase (CK), lactate dehydrogenase (LDH), myoglobin (MYO), alanine transaminase (ALT), c-reactive protein (CRP) and interleukin-6 (IL-6) have been considered metabolic indicators of muscle damage and concomitant inflammation, both of which occur after strenuous, mainly eccentric exercise ( 19 ). However, there are only two studies without exercise intervention that examined recovery-related blood markers after CP supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…Athletes can compete with enjoyment if they have a good recovery, which can enhance sleep quality, decrease fatigue, and reduce DOMS [15]. The bulk of earlier research on the recovery aspects of soccer games only looked at male athletes' game responses; however, women could also be the subjects of this research to find out how changes in biomarkers of muscle damage and physical performance occur after soccer games [16]. The fact that estrogen, for instance, has been demonstrated to have a protective effect on reactive oxygen species (ROS) is another reason for conducting this research.…”
Section: Introductionmentioning
confidence: 99%